2021
DOI: 10.1021/acs.chemrev.0c01265
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Proactive Design of Sustainable Chemicals: Ionic Liquids as a Prime Example

Abstract: The tailorable and often unique properties of ionic liquids (ILs) drive their implementation into a broad variety of seminal technologies. The modular design of ILs allows in this context a proactive selection of structures that favor environmental sustainabilityideally without compromising their technological performance. To achieve this objective, the whole life cycle must be taken into account and various aspects considered simultaneously. In this review, we discuss how the structural design of ILs affects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 384 publications
2
57
1
Order By: Relevance
“…These results stay in contrast with the conclusion presented in a very recently published review that polar substituents reduce toxicity. 33 On the other hand, cytotoxicity data toward HeLa and A549 cell lines (see again Table S1) reported by Jovanovic-Santa et al 34 are consistent with this rule. The results are different for each cell line.…”
Section: ■ Results and Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These results stay in contrast with the conclusion presented in a very recently published review that polar substituents reduce toxicity. 33 On the other hand, cytotoxicity data toward HeLa and A549 cell lines (see again Table S1) reported by Jovanovic-Santa et al 34 are consistent with this rule. The results are different for each cell line.…”
Section: ■ Results and Discussionmentioning
confidence: 65%
“…Additionally, one can note based on Wang et al 22 results that the structure of the cation (ammonium, pyridinium, or imidazolium) with a similar number of -CH 2groups attached to nitrogen does not influence toxicity toward HeLa cells significantly, which is consistent with our previous observation for NHDF cell lines even if aliphatic quaternary ammonium ILs have been reported to be less hazardous in many other cytotoxicity studies. 33 However, importantly, not only does the elongation of the alkyl chain length exert influence but also cation/anion functionalization may play a role, as clearly seen in the results presented by Jovanovic-Santa et al 34 or Ferraz et al 35 (see Table S1). Ferraz et al 35 showed that ILs with hydroxyl-functionalized cations ([C 2 OHC 1 im] + ) are much more cytotoxic against HepG2 cells than ILs with nonfunctionalized cations ([C 2 C 1 im] + ).…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…Ionic liquids are usually described as chemically stable, but, of course, this statement has exceptions and limitations. This is particularly true in the case of IL solutions in water, which can drive hydrolization processes [ 4 , 160 ]. Another important degradation process, especially important for cations, is photo-oxidation, which, however, besides negative effects, could also have a positive role in removing residual ILs in waste products.…”
Section: Applicationsmentioning
confidence: 99%
“…Therefore, intensive biomass washing after pretreatment before the hydrolysis step is crucial to ensure the full efficiency of cellulase function, and this washing leads to an increase in wastewater treatment cost, complexity in neutralization, and difficulty in the solid–liquid separation process. Different strategies were proposed to lessen IL toxicity, such as using low toxic IL, high tolerant enzyme and microorganism, and diluted IL [ 19 ].…”
Section: Introductionmentioning
confidence: 99%